2020
DOI: 10.1017/s1047951120001638
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in adult patients with CHD: a matter of anatomy or comorbidities?

Abstract: Little is know about COVID-19 outcome in specific populations such as Adult congenital heart disease (ACHD) patients. We report three cases of adult patients with similar underlying disease with completely different clinical severity at the time of COVID-19 infection. The patient with the most severe clinical course was obese and diabetic, suggesting that COVID-19 mortality and morbidity in Adult congenital heart disease patients might be independent of anatomic complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 6 publications
2
12
0
1
Order By: Relevance
“…We identified 19 papers of which 12 were guidelines, commentary, or opinion and 7 included patient data ( Table 1). We included the 7 papers, [2][3][4][5][6][7][8] which contained actual patient data and this included a variety of case reports, case series, and retrospective reviews. We excluded the 12 papers 9-20 that did not include any patient data and were deemed guidelines, opinion pieces, or a commentary.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 19 papers of which 12 were guidelines, commentary, or opinion and 7 included patient data ( Table 1). We included the 7 papers, [2][3][4][5][6][7][8] which contained actual patient data and this included a variety of case reports, case series, and retrospective reviews. We excluded the 12 papers 9-20 that did not include any patient data and were deemed guidelines, opinion pieces, or a commentary.…”
mentioning
confidence: 99%
“…A total of 94 suspected or confirmed cases have been reported in 7 papers. [2][3][4][5][6][7][8] By far, the biggest published series is from Italy 2 with 76 patients included. Amongst the 94 reported cases of CHD and COVID-19 infection, 79 patients (84%) were adults and 15 (16%) were children.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the exclusion of duplicates, 12 articles were selected for inclusion into the analysis (Fig 1). [11][12][13][14][15][16][17][18][19][20][21][22] These comprised a total of 143 patients, of which 99 had CHDs. The key information from each article is summarised in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…29 Although, Ferrero et al demonstrated how the clinical course of COVID-19 can vary in patients with similar physiology and anatomy. 14 A study outlined the categories of children with CHD that would be at increased risk of severe illness if they acquired a COVID-19 infection. These included patients with a large VSD, "single heart physiology" such as hypoplastic left heart syndrome and tricuspid atresia, and patients who had an upcoming surgical procedure or had already undergone one, including the Fontan procedure.…”
Section: Is There a Correlation Between Specific Chd And Covid-19 Outmentioning
confidence: 99%